A GRAVITY PROFILE OF THE LOWER BENUE TROUGH OF NIGERIA (1976)
Gravity measurements were made along a roughly east-west profile across the lower Benue trough, with the main objectives of investigating the nature and configuration of the basement beneath the trough and determining the thickness of the sedimentary cover rocks. I87 gravity stations were established at 2-4km intervals and standard corrections were applied to the observed gravity values. A Bouguer gravity map of the whole Benue trough is compiled from the results of these measurements and data obtained from previous works. The map shows that the positive anomaly along the axis of the trough is a most prominent regional feature that extends over the whole length of the trough. The abrupt truncation of the positive anomalies along a NNE-SSE line may represent the Cretaceous continental margin. The axial positive is ascribed to the doming of the basement underlying relatively dense Albian Shales and their associated intermediate to basic intrusives along the trough axis as a result of tectonic processes. "Growth” of the positive anomaly towards the South is attributed to the basement being at a shallower depth in the lower Benue than in the upper Benue trough and to the probability that oceanic crust underlies the sediments at the southwestern end of the trough. The negative anomalies are due to thick sedimentary sequences which fill the flanks of the trough. The sediments are estimated to have a maximum thickness of 4.25km in the surveyed area of the lower Benue trough.